What Can We Learn about Country Performance from Conditional Comparisons across Countries? - Ravallion, Martin (World Bank, Washington, DC, 2014)
There have been many attempts to infer latent performance attributes of governments (or other institutions) from conditional comparisons that control for observed variables. Success in doing do could greatly improve government performance. The author critically reviews the econometric foundations of the methods used. He argues that latent heterogeneity remains a fundamental, but unresolved problem. Locating a benchmark for measuring performance, adds a further problem. Current methods do not yield a consistent estimate of even the mean latent performance attribute. An assessment of country performance by these methods could well be wildly wrong.